German R&D-intensive industries: Value added and productivity have recovered considerably after the crisis - Heike Belitz; Martin Gornig; Alexander Schiersch (DIW Economic Bulletin, 2011)
No large industrialized nation is as strongly specialized in the production of R&D-intensive goods as Germany. In the crisis year 2009 these export-oriented industries had to pass a crucial test. The slump in sales endangered both specialized jobs and the financing of high R&D expenditures, and thus the ability of these industries to compete technologically in the future. The Commission of Experts for Research and Innovation (Expertenkommission Forschung und Innovation - EFI), which regularly informs the German government about the status and prospects of Germany's technological performance, requires early indications about the development of R&D-intensive industries. Detailed comparative international data regarding industrial development, such as the EU KLEMS Datenbasis and the OECD STAN data, is only available with a lag of two to three years. This is why the DIW has estimated the value added and the volume of labour input for R&D-intensive industries in Germany, the US, Japan, France and the UK for the period from 2008 to 2010. This extended database is used to analyze the development of production and labour productivity up to the present.
Keywords: O14; O40; O57; 330; industrial specialization; international trade; manufacturing industries